Efektivitas Pembelajaran Kitab Mukhtashar Ilmu Tajwid li al-Nasyi'in dalam Meningkatkan Kemampuan Membaca Al-Qur'an Santri - Badrus Shalih; Marzuqi Marzuqi; Zainal Abidin (YASIN, 2026)
Textbook-based tajwid learning is an important strategy for improving the quality of students’ Qur’an recitation, particularly in the context of pesantren education. This study aimed to examine the effectiveness of using Mukhtashar Ilmu Tajwid li al-Nasyi’in in improving students’ Qur’an reading ability at Pondok Pesantren Darullughah Wadda’wah (Dalwa). This study used a descriptive qualitative approach focusing on the experiences of students and ustaz in the routine tajwid learning process. The research subjects consisted of 40 students aged 14–18 years and three teaching ustaz. The research design comprised three stages, namely pre-intervention, intervention, and post-intervention, with learning methods including talaqqi, musyafahah, demonstration, drill, and murojaah. The results showed that the use of Mukhtashar Ilmu Tajwid li al-Nasyi’in helped students master makharijul huruf, sifatul huruf, the rules of nun sukun and tanwin, the rules of mim sukun, mad wal qashr, qalqalah, as well as waqaf and ibtida’. Although there were challenges in the form of heterogeneous initial abilities among students and limited time allocation, the combination of structural textbook-based learning methods proved effective in improving the accuracy of tajwid rule application and the quality of students’ Qur’an recitation. These findings provide a practical contribution to the development of tajwid learning in pesantren through the use of systematic textbooks and learning methods oriented toward recitation accuracy.